Effects of Square-Stepping Exercise on balance and depressive symptoms in older adults - Jessica Rodrigues Pereira; Sebastião Gobbi; Camila Vieira Ligo Teixeira; Carla Manuela Crispim Nascimento; Danilla Icassatti Corazza; Thays Martins Vital; Salma Stéphany Soleman Hernandez; Florindo Stella; Ryosuke Shigematsu (Universidade Estadual Paulista (UNESP), 2014)
The aim of this study was analyze the effects of Square-Stepping Exercise (SSE) on depressive symptoms, balance and functional mobility in older adults. Participants were distributed into two groups: Trained Group (TG), who performed a 16-week intervention with SSE and Control Group (CG), who performed only evaluations. The Berg Balance Scale and Time Up and Go Test (TUG) constituted the evaluation protocol to verify balance and functional mobility. Geriatric Depression Scale-short form (GDS-15) was applied for measure depressive symptoms. Evaluations were realized pre and post 16-week. Significant improvements were observed in the TG with the maintenance of GDS-15 scores and on the time to perform the TUG test which reflects better functional mobility than the CG. This could lead to conclude that the SSE is an important tool for improve balance, prevent falls and decrease depression symptoms.